China a history - Keay, John. ([S.l.] : HarperPress, 2010)
Three thousand years of Chinese history in an accessible and authoritative single volume. Despite the recent rise of China to a position of dominance on the world economic stage, Chinese history remains an elusive subject. Yet it is this vast narrative of appalling loss, superhuman endeavour and incredible invention that has made China the superpower it is today. From the dawn of legend to the succession of great dynasties, from Confucius to Chairman Mao and from the clamour of revolution to the lure of slick capitalism, John Keay takes the reader on a sweeping tour through Chinese history. This is a definitive and indispensable account of a country set to play a major part in our future.
Kindle eBook.
Keywords: China